Solid-state fermentation of Ulva Rigida for production of cellulases, xylanases and ß-glucosidase - Fernandes, Helena (2018)
Seaweeds are important organisms in marine ecosystems, are included on blue biorefinery category and they are rich in different polysaccharides, that can induce enzyme production by solid-state fermentation (SSF). Ulva rigida was used as substrate in SSF to produce cellulases and xylanases and to increase its protein content. The SSF were performed with previously washed and with unwashed seaweed by Aspergillus ibericus. Xylanase and cellulase activities were higher in fermented unwashed seaweed, correspondingly 359.8±6.1 U/g dry substrate and 59.9±2.4 U/g, respectively. In fermented washed U. rigida, these values achieved 212.4±17.7 U/g and 43.6±3.7 U/g, respectively. -glucosidase activity was similar in washed seaweed (6.94±0.21 U/g) and in unwashed seaweed (6.87±0.18 U/g). After SSF, protein content of unwashed seaweed was increased by 14%. Unwashed U. rigida resulted in better enzymatic activities, being a promising option to produce these commercially-valued enzymes.